French palace oratories and two-story residential chapels in Silesia. A Polish accent against the background of European religious architecture in the context of the Sainte-Chapelle model - Barbara Pierścionek; Justyna Kleszcz (Cogent Arts & Humanities, 2025)
Regarding the construction of two-story churches in Europe during the Middle Ages, as researched by the authors, it is impossible to ignore chapels, which are part of the royal or princely residential complexes. Two-story religious buildings were erected at the end of antiquity until the end of the Middle Ages. They are an interesting issue, but they still leave much confusion about the functional model used. This article describes the topic of the two-story castle and palatine chapels raised in Silesia (the land situated in Poland, Bohemia, and Germany) in the context of a contemporary pattern based on the Parisian Sainte-Chapelle chapel in Europe. The research showed an indirect transfer of stylistic patterns of the Sainte-Chapelle model due to the change in their functional layout to single-nave chapels (in Trzebnica and Racibórz), as they were the repetition of forms from neighboring countries (Germany, Austria, Bohemia, and Moravia).